Nonlinear optical imaging investigations at the micro-scale - Lim, Ken Choong (2015)
The development and commercial availability of ultrafast femtosecond lasers with high peak power enabled strong optical fields to be generated in a straightforward manner. Since then, nonlinear optics and nonlinear optical imaging has proven to be an effective tool for investigation and analysis of various samples in biology, microelectronics and other domains. In this project, a Nonlinear Laser Scanning Microscope (NLSM) is setup, aligned and calibrated in order to image various samples of organic and inorganic origins. Using the NLSM, nonlinear optical images from SLS, Native and FLS collagen structures were obtained and correlated with their linear optical signals to obtain nonlinear optical signatures of the collagen structures. In addition, nonuniform SHG signal distribution from native collagen fibers were observed, an effect plausibly due to SHG geometric resonance. Uniformly distributed TPEF signals were detected in SLS and FLS collagen structures, providing preliminary evidence for the uniform incorporation of glycoprotein and ATP in the ultrastructures of FLS and SLS collagen respectively. Furthermore, the NLSM was used to perform 3D tomographic imaging on electroluminescent displays printed on a plastic substrate. Image blurring and distortions were discovered to be caused by birefringence induced astigmatism originating from the plastic substrate. Simulations were performed to correlate the experimentally observed phenomena to a proposed analytical model and methods to reduce image distortions due to astigmatism are briefly discussed. Lastly, in order to further extend the capabilities of the NLSM, a methodology to batch stitch images obtained using an NLSM was developed to achieve wide field-of-view 3D tomography.